Strategi Pembelajaran Matematika Berbasis Pemahaman Konsep pada Siswa kelas IV di SDN 03 Kanigoro Kota Madiun - Laora Gita Nabila; Abidah Ardelia Maghfiroh; Soniya Regina Putri Wahyudi; Rusmawati Agnez Khuzayma; Valentino Satria Wibowo (Universitas PGRI Madiun, 2026)
This study aims to examine teacher strategies in directing mathematics assignments in elementary schools as an effort to improve student learning independence, in helping students understand mathematical concepts, and analyze the problem of the large amount of mathematics material in Indonesia on students' level of understanding. The research method used is descriptive qualitative with in-depth interviews with mathematics teachers who are also homeroom teachers of grade IV SDN 03 Kanigoro, Madiun City. The results show that the assignment strategy implemented in class can reduce students' dependence on the internet and AI-based applications, thereby encouraging students to think critically and independently. In addition, explanations of real-life connections have proven effective in strengthening the understanding of mathematical concepts, because students can see the logical relationship between procedures and results that are relevant to everyday life. However, the complexity and large amount of mathematics material in the curriculum often become obstacles, making it difficult for students to fully understand each concept. Therefore, teachers need to select essential materials and present them with a contextual approach and based on concept recognition so that students are not only able to solve problems, but also understand the basic concepts that form the foundation of learning at the next level